Synthesis, characterization, and lithium storage capability of AMoO4 (A = Ni, Co) nanorods - Xiao, Wei (2012)
One-dimensional (1D) AMoO4·nH2O (A = Ni, Co) nanorods have been synthesized by a facile hydrothermal method. The effect of different synthetic conditions on the morphologies of the final products was systematically investigated. The size of the nanorods can be easily controlled by adding ethanol in the synthetic solution. For the first time, the self-assembled growth of oriented NiMoO4·nH2O nanorod arrays on Ti-foil substrates was achieved. The thermal dehydration and phase transformation processes of AMoO4·nH2O nanorods were thoroughly investigated by TG-DTA and time-resolved synchrotron XRD. As-prepared hydrate nanorods can be further converted to corresponding AMoO4 nanorods by annealing at 300−600 °C for 1 h without significant alteration of 1D morphology. Electrochemical lithium storage capabilities of dehydrated AMoO4 nanorods have been investigated. The results suggest their potential use as cathode materials for lithium ion batteries.